The COMBINE Trial: Treatment of Alcohol Dependence from Bench to Bedside - Busse, Gregory (MD Conference Express, 2007)
In this article, leading alcohol researchers present the most recent findings from the COMBINE Trial, a multicenter, treatment comparison study funded by the National Institute on Alcohol and Alcohol Abuse.